Nodule in mesosalphinx: a rare microscopic finding - Jain, Sunila; Karmacharya, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ectopic adrenal cortical rests are uncommon in adults, particularly in females. Their occurrence in fallopian tubes or mesosalphinx is extremely rare. Herein, we report a rare occurance of ectopic adrenal cortical rests in mesosalphinx which was diagnosed on histopathological examination. To the best of our knowledge, there are less than five previously published cases at this rare location and the present report is the second case from India. A 46-year-old female who underwent hysterectomy for fibroids was incidentally detected with ectopic adrenal cortical rests in the mesosalphinx on histopathology. The present case is reported to increase the awareness of this unique finding at this rare location, its implications and histopathological diagnosis.